Gene3D: a domain-based resource for comparative genomics, functional annotation and protein network analysis - Lees, Jonathan; Yeats, Corin; Perkins, James Richard; Sillitoe, Ian; Rentzsch, Robert; Dessailly, Benoit H; Orengo, Christine A. (Oxford University Press, 2012)
Gene3D http://gene3d.biochem.ucl.ac.uk is a comprehensive database of protein domain assignments for sequences from the major sequence databases. Domains are directly mapped from structures in the CATH database or predicted using a library of representative profile HMMs derived from CATH superfamilies. As previously described, Gene3D integrates many other protein family and function databases. These facilitate complex associations of molecular function, structure and evolution. Gene3D now includes a domain functional family (FunFam) level below the homologous superfamily level assignments. Additions have also been made to the interaction data. More significantly, to help with the visualization and interpretation of multi-genome scale data sets, we have developed a new, revamped website. Searching has been simplified with more sophisticated filtering of results, along with new tools based on Cytoscape Web, for visualizing protein-protein interaction networks, differences in domain composition between genomes and the taxonomic distribution of individual superfamilies.
Keywords: Proteínas-Bases de datos; Proteínas-Clasificación; Databases, Protein; Molecular Sequence Annotation*; Protein Structure, Tertiary*; Proteins / classification; Genomics